2018
DOI: 10.1080/10410236.2017.1422099
|View full text |Cite
|
Sign up to set email alerts
|

Altering Adolescents’ Pre-Bedtime Phone Use to Achieve Better Sleep Health

Abstract: Mobile phone use is often blamed for adolescent sleeping difficulties in the popular and scientific literature, with correlations observed between adolescents' mobile phone use and their bedtime. We aimed to obtain experimental evidence to support these causal claims. A within-subjects experiment (baseline, intervention) was conducted in adolescents' homes, to determine the effect of restricting adolescents' pre-bed mobile phone use on school night sleep habits. Following a baseline week, adolescents were give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 54 publications
5
66
1
1
Order By: Relevance
“…Sleep quality was improved significantly. This was consistent with the results of a previous study which found that adolescents who stopped using their phones 80 min earlier and turned their lights off 17 min earlier, slept 21 min longer after one week of phone usage restriction [17]. This implies that limiting the use of mobile phones before bedtime could effectively improve sleep.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Sleep quality was improved significantly. This was consistent with the results of a previous study which found that adolescents who stopped using their phones 80 min earlier and turned their lights off 17 min earlier, slept 21 min longer after one week of phone usage restriction [17]. This implies that limiting the use of mobile phones before bedtime could effectively improve sleep.…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, only Harris et al investigated the effect of restricting the use of electronic media after 22:00 in high school athletes, and they did not find any improvement in sleep habits, athletic performance, cognitive performance, or mood after four weeks of this intervention [16]. Meanwhile, another study assessed the impact of restricting phone use for one hour before bedtime and found that this restriction could advance lights-out time and increase total sleep-time [17].…”
Section: Introductionmentioning
confidence: 99%
“…Health promotion work to reduce sleeping difficulties caused by technology use might be complex. Bartel, Scheeren and Gradisar restricted adolescents’ prebed mobile phone use with one hour before bed on school nights, and it led to turning the lights off earlier and sleeping longer. However, adolescent recruitment for that study was low, indicating that adolescents lacked motivation for negotiating changes to their evening phone use.…”
Section: Discussionmentioning
confidence: 99%
“…However, adolescent recruitment for that study was low, indicating that adolescents lacked motivation for negotiating changes to their evening phone use. According to Bartel, Scheeren and Gradisar motivating interviews or other cognitive strategies are required to decrease adolescents’ mobile phone use. School nurses and professionals in school health services must lead these important dialogues, as they occupy a unique position in the adolescents’ everyday life.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional analyses are prevalent in this research area, with calls for longitudinal and experimental work to enrich current understanding 56 57 . Recent studies on general technology use have supported bidirectional links between higher technology use and shorter sleep in adolescents 58 , with evidence that restricting phone access can advance bedtimes and extend sleep opportunity 59 . Restricting adolescent social media use is likely to be especially challenging, as this is a developmental period of increasing autonomy during which peer interactions, belonging and acceptance are highly valued 2 .…”
Section: Limitationsmentioning
confidence: 99%